Clinical Dental Midline Shift Is Not a Predictor of the Side of Shorter Hemimandible: A Cone Beam Computed Tomography Diagnostic Study - Lígia Pereira da Silva; Alicia López-Solache; Urbano Santana-Penín; José López-Cedrún; María Jesus Mora; Pablo Varela-Centelles; Antonio González-Mosquera; Almudena Rodríguez-Fernández; Urbano Santana Mora (Diagnostics)
Background/Objectives: Interincisive midline deviation is frequent. Determining the cause (dental versus skeletal) is crucial for treatment planning. This study assessed the null hypothesis that neither clinical dental midline shift nor the temporomandibular disorder (TMD)-affected side correlate with maxillary/mandibular asymmetry. Methods: Thirty-eight CBCT scans were analyzed: thirty-five (92.1%) females, three (7.9%) males; mean (SD) age 34.6 (11.9) years old. Tomographic images were acquired using the i-CAT® Imaging System; mandibular/maxillary measurements were obtained with the Planmeca Romexis® software v.6.This is an ancillary study of a clinical trial (NCT02144233) that included chronic pain (TMD diagnosis; DC/TMD criteria), fully dentate, and stable normo-occlusion participants. Results: We found sixteen (42.1%) dental midline deviations to the right and thirteen (34.2%) to the left. In the study population, the right side was more developed: a hemimandible length of 119.4 (5.7) mm versus 118.6 (5.3) mm for the right and left sides, respectively (95% CI 0.21 to 1.51), p = 0.01. Conclusions: Neither the dental midline shift side nor the affected side predicted a less developed hemimandible.